O que é “ontologia do presente”? (Nuntius Antiquus, 2010)
This paper’s aim is to elucidate the meaning of the paradoxical expression “ontology of the present”, utilized by Foucault in his latest works. To achieve this goal, I adopted a twofold strategy: on the one hand, it was useful to recall that this was not the first time Foucault used a deranging expression. In the 1960’s, in the period he developed his “archeology of knowledge”, we can find in some of his major works the husserlian term “historical a priori”. On the other hand, I had to analyze some aspects of his interpretation of the modernity that we can find in his last articles, interviews and lessons in the Collège de France. In these occasions, Kant’s philosophy was the main theoretical influence.